MATRIKS TRANSFORMASI OPERATOR VECD* MENJADI VECH^ - Alsbaldo, Yuco; Yanita, Yanita; Yulianti, Lyra (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
This article discusses a new matrix operator that is constructed differently from the vech operator and the vecd operator by stacking the main diagonal entries (supra-diagonal) and entries of a square matrix. This operator, called  operator, explicitly constructs a matrix that transforms  into , where  is an  square matrix, and then obtains the properties of the transformation matrix